Rukshah Yang Merusak Makna Perkawinan: Tinjauan Hukum Kawin Mut’ah dari Perspektif Hukum Islam - Bhisma Putra Rozi, Zulfiqar; Islami, Nurul (Universitas Islam DDI AG.H. Abdurrahman Ambo Dalle, 2026)
Rukshah is defined as a concession in carrying out Islamic law by observing certain conditions. The legal consequence for someone who receives rukshah is that they are permitted to refrain from or do something that is essentially contrary to sharia. Currently, there is a phenomenon of mut'ah marriage among Indonesian Muslims. Historically, the basis for its validity is that Mut'ah Marriage is considered one of the rukshah in marriage, which is still debated regarding its permissibility and legality. This study uses a normative juridical method with a conceptual and historical approach to examine the true meaning or essence of the concept of rukshah so that it can answer whether current conditions can still be categorized as rukshah for performing mut'ah marriage. The results of the study show, using the principle of maqasid al syari'ah, that rukshah can only be given in emergency situations to maintain the public interest and the current condition cannot be interpreted as an emergency, so it is forbidden to perform mut'ah marriage.